Tuning magnetic properties for domain wall pinning via localized metal diffusion - Jin, Tianli (2018)
Precise control of domain wall displacement in nanowires is essential for application in domain wall based memory and logic devices. Currently, domain walls are pinned by creating topographical notches fabricated by lithography. In this paper, we propose localized diffusion of non-magnetic metal into ferromagnetic nanowires by annealing induced mixing as a non-topographical approach to form pinning sites. As a first step to prove this new approach, magnetodynamic properties of permalloy (Ni80Fe20) films coated with different capping layers such as Ta, Cr, Cu and Ru were investigated. Ferromagnetic resonance (FMR), and anisotropy magnetoresistance (AMR) measurements were carried out after annealing the samples at different temperatures (T an ). The saturation magnetization of Ni80Fe20 film decreased, and damping constant increased with T an . X-Ray photoelectron spectroscopy results confirmed increased diffusion of Cr into the middle of Ni80Fe20 layers with T an . The resistance vs magnetic field measurements on nanowires showed intriguing results.